KINERJA PEGAWAI BIDANG KEBUDAYAAN PADA DINAS PENDIDIKAN DAN KEBUDAYAAN PROPINSI SULAWESI TENGAH - Nurnaila, Nurnaila (Katalogis, 2015)
This research aims at describing the effectiveness of the employees’ permormance in the field of culture, department of Education and Culture Central Sulawesi Province. This research used qualitative descriptive method. The five were collected through observation, interview and documentation. The five informans of this research were taken through sampling technique. The results show that the employees’ performance in the field of Culture at departmen of education and culture Central Sulawesi Province in not optimum. Based on the work indicator proposed by Dwiyanto, it can be concluded that the employees’ performance were influenced by : 1) productivity of the employees in the field of culture is optimum. 2) quality of services of the employess is not optimum. 3) responsivity of the employees is optimum. 4) The responsibility of the employees is optimum, and 5) The accuntability of the employees is optimum.